Risk management in resilient supply chain - Goh, Hong Chew. (2012)
In this report, different types of risks have been identified and analyzed. These risks contribute to the vulnerability of a supply chain and they are subjected to the occurrence of major disruptions. In view of that, creating resilience in a supply chain is discussed. Next, risk management in a resilient supply chain is reviewed together with a comprehensive list of robust strategies to be implemented. These robust strategies allow a supply chain to operate and manage risks efficiently and effectively in the event when any of the different types of risks occur. Risk management in a resilient supply chain revolves around flexibility, redundancy, efficiency, effectiveness and different trade-offs. Implementation of risk management strategies requires a certain amount of money to be invested. Hence, a mathematical modeling is developed to calculate the optimal amount of money to be invested and the expected revenue that the supply chain is able to profit. Equipping with these information as well as the managerial styles and experiences, the management is subsequently capable of deciding a well-balanced risk management strategy to be implemented to the supply chain based on an reiteration process.